Inovasi Strategi Pembelajaran Untuk Menumbuhkan Kesadaran Keagamaan Di SMP 49 Medan - Yusmeini, Dinda (Yayasan Rahmat Islamiyah, 2024)
This study aims to develop innovative teaching strategies that effectively foster religious awareness among students at SMP 49 Medan. Religious awareness is a crucial aspect of character education, especially in shaping students’ attitudes and behaviors in alignment with religious values. The research method used is classroom action research (CAR) with a qualitative approach. The innovation process involves developing collaborative learning strategies, interactive discussions, and personal reflection, tailored to the students’ needs in understanding and internalizing religious values. The results of the study indicate that these innovative strategies successfully enhance students' religious understanding and practices, as reflected in the increased frequency of worship and active participation in school religious activities. Furthermore, the interactive and relevant learning approach encourages students to better understand religious values in the context of everyday life. This study concludes that implementing innovative teaching strategies can be an effective alternative for fostering religious awareness among junior high school students, and it makes a positive contribution to character education. Recommendations are provided for teachers to continue innovating in developing appropriate methods to enhance religious awareness in the school environment.